"The African family is large, very large" mobility and the flexibility of kinship – examples from Cameroon. (September 2020) - Geschiere, Peter
When I started fieldwork among the Maka in SE Cameroon in 1971 I was suprised that for them kinship was hardly about ascribing people a fixed position. In retrospect this makes me realize how deeply Talcott Parsons' famous pattern variables – notably 'ascription' versus 'achievement' influenced our perspective. But Maka people turned out to be true masters in 'working'-with kinship, constantly 'discovering' kin in unexpected contexts, making creative equations and switch-es. My subsequent research in the area (up till now) highlighted how over time this plasticity of their kinship arrangements increased with growing urbanization and even more with transcontinental migration. Cameroon's famous 'bush-fallers' have developed their own ways for 'working' with kinship. However, this plasticity should not only be studied as stemming from new and shifting conditions. I hope to show as well that such a more dynamic view on kinship is valuable for re-evaluating classical kinship theory.